Risk factors for placenta previa among pregnant women of Kyiv, Ukraine: a retrospective cohort study - V.O. Berestovyi; O.V. Zelinska; N.V. Gerevich; D.O. Govsieiev (Сучасна педіатрія: Україна, 2023)
Placenta previa is a significant obstetric problem with elevated morbidity and mortality rates for both mother and fetus. The risks associated with placenta previa underscore the necessity for comprehensive treatment and timely intervention to mitigate adverse outcomes.